PENGARUH PENGGUNAAN FLIP CHART (LEMBAR BALIK) TERHADAP HASIL BELAJAR SENI RUPA SISWA SMPN 2 PANCUNG SOAL KABUPATEN PESISIR SELATAN TAHUN AJARAN 2019/2020 - Reno Tiora; Yofita Sandra (Serupa The Journal of Art Education, 2020)
This research is motivated by the low student learning outcomes because the learning media used by educators have not been effective. This is compounded by the lack of information and the teacher has not used Flip Chart media in Fine Arts learning. The solution that can be offered to overcome this problem is by applying Flip Chart media. This study aims to determine the learning outcomes of students taught with Flip Chart learning media with students taught without Flip Chart learning media in SMP N 2 Pancung Soal Kabupaten Pesisir Selatan 2019/2020. This type of research is a Quasi Experimental research with Posttetsonly Control Group research design. The population of this study were all students of class VIII in 2019/2020 Academic Year totaling 150 people. The sampling technique in the form of simple random sampling with selected samples is students of class VIII2 as the Experiment class and class VIII1 as the control class which is determined first through the normality test, homogeneity test, and variance analysis. Based on the results of the study obtained an average value of student learning outcomes for the Experiment class is 87.00 and for the control class is 76.00. In this study a hypothesis test was used: tarithmetic> ttable then H0 was rejected and Hi was accepted. After testing the hypothesis with one-way t-test obtained tarithmetic> ttable (8,610> 2.04523) then the research hypothesis is accepted. It can be concluded that student learning outcomes taught by Flip Chart Learning Media are higher than  student learning outcomes taught without Flip Chart learning media at SMP N 2 Pancung Soal Kabupaten Pesisir Selatan.Keywords: student learning outcomes, Flip Chart media